Sustainability Analysis of Kopiko Using SWOT Analysis - Nurlia, Siti Adinda; Adhy Priyo Pambudi; Julian Pinaria; Ovalia Rukmana (CV. ULIL ALBAB CORP, 2026)
In the highly competitive Fast Moving Consumer Goods (FMCG) industry, long-term brand sustainability has become a strategic phenomenon worthy of in-depth examination. Shifts in consumer preferences, increasing awareness of health-related issues, evolving global food regulations, and intensifying competitive pressures require companies to adopt adaptive and sustainable strategies. This study aims to analyze Kopiko’s existence strategy over more than five decades by employing SWOT analysis as the primary strategic framework, strengthened by VRIO analysis and Porter’s Five Forces. The research adopts a descriptive qualitative approach, utilizing secondary data sourced from the annual reports of PT Mayora Indah Tbk for the 2019–2024 period, official company publications, as well as academic journals and strategic management reference books published within the last seven years. Data collection was conducted through documentation review and literature study, while data analysis employed content analysis integrated with VRIO, Five Forces, SWOT, the TOWS Matrix, and the qualitative development of a risk register. The findings indicate that Kopiko’s core strengths lie in its strong global brand equity, its unique positioning as the world’s first coffee candy, and the organizational support and international distribution network of PT Mayora Indah Tbk. Key opportunities arise from the growth of the FMCG industry in emerging markets, global coffee consumption trends, and the expansion of digital marketing. Nevertheless, Kopiko faces significant challenges, including health-related concerns associated with sugar content, increasing international food regulatory pressure, and intensifying global competition. Through the TOWS Matrix and risk register, this study formulates strategies to strengthen Kopiko’s long-term existence through low-sugar product innovation, the reinforcement of authentic brand differentiation, and the enhancement of strategic risk management. This research is expected to contribute academically to the study of brand existence strategies in the FMCG industry and to serve as a practical reference for companies in sustaining long-term business performance.